VERNACULAR ANSWERS TO SPATIAL NEEDS OF HUMAN ACTIVITIES: INDONESIAN HOUSES - Zuber Angkasa Wazir; Irma Indriani (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2019)
The process of building traditional houses requires sizes of activities to determine dimensions of spaces. This study seeks to reveal how the activities of occupants relate to the dimensions of space in the vernacular society in Indonesia. It uses a literature study approach by reviewing various studies on vernacular housing in Indonesia. A total of 18 vernacular houses were reviewed and compared to find common relations between the activities and dimensions of the vernacular space. It was found that there were high variations in various placements, uses, and relations between activities and human living spaces, influenced by anthropometric factors, location, and socio-cultural factors. There are a very flexible space utilization and very rigid space utilization and between the two. This finding is expected to be a material for the development of simple, mass-built houses considering the habits of local residents in their activities.